Graham-Little-Piccardi-Lassueur syndrome-A rare case report with concomitant lichen planus pigmentosus and oral lichen planus in a pregnant female - Abhishek S Patokar; Gaurav H Khandait; Nitin Chaudhari; Swapna S Khatu (Wolters Kluwer Medknow Publications, 2022)
Graham-Little-Piccardi-Lassueur syndrome is a rare variant of lichen planopilaris. It is characterized by multifocal, patchy, cicatricial alopecia of the scalp, noncicatricial alopecia of axilla and pubic region, and keratotic follicular papules involving the trunk and extremities. Trichoscopy shows perifollicular erythema, tubular perifollicular scales, fibrotic white dots, and hair casts along the hair shafts. We are reporting this rare syndrome in a 26-year-old pregnant woman with concomitant oral lichen planus and lichen planus pigmentosus. This case is unique as no previous report of coexistence of these variants of lichen planus has been published.